Tactical portfolios : Strategies and tactics for investing in hedge funds and liquid alternatives - McCann, Bailey; Wiley eBooks; Opalesque (Firm) (Hoboken, New Jersey : Wiley, 2014)
Take an active management approach with liquid alternatives to increase R.O.I. Take advantage of inefficiencies in the market by investing in alternative assets. Hedge fund and private equity investment diversifies your portfolio and helps shield you from market volatility, allowing your more passive assets to work the long game. In Tactical Portfolios: Strategies and Tactics for Investing in Hedge Funds and Liquid Alternatives, author Bailey McCann guides you through the principles of hedge fund investment and the associated philosophies of risk management strategies. McCann's.
Understanding Managed Accounts-By Chidem KurdasManagers' Objections; Food for Thought: Consider Managed Futures Investing in a Fashion Similar to Growth Stock Investing; Summary; Notes; Chapter 7 Investment Mechanics; Diversification: Real and Imagined; Evaluation of Risk; The Hedge Is the Edge-Types of Hedges; Short Trade; The Paradox; What Color Is Your Swan?; Cash Is Not Always King; Evolution; Structure; Are Puts the Only Option?; Volatility; Tail Risk Hedges for Retail Investors; Derivatives; Summary; Notes; About the Author; About the Contributors; Additional Resources; Index.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Hedge funds; Investments; Finance; Hedge funds; Investments; Risk management; BUSINESS & ECONOMICS -- Finance; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Hedge funds; Investments; Electronic books